Role of ICT in Teacher-Student Communication during Covid-19 in Pakistan - Quratulain; Parveen, Zahida; Ghazanfar, Shaista (Pakistan Journal of Humanities and Social Sciences, 2023)
ICT tools provided an alternative and effective direction to teaching and learning during COVID. The goal of this research is to investigate the effects of ICT on teacher-student communication during COVID-19. Quantitative research design was employed. A sample size of 40 teachers and 100 students from four public secondary schools was selected. Data were gathered through a closed-ended questionnaire carrying 14 statements. Purposive sampling was used. Data were analyzed through SPSS software. Standard deviation and independent sample t-test were run. Overall, it was found that all participants (teachers and students) find ICT tools useful in teacher-student communication but there were difference of opinion between male and female teachers about the role of ICT in communication based on different applications whereas male and female students showed similar responses.